The Influence of Student Engagement Towards Learning Achievement of Creative Industry Telkom University Bandung - Sofah Tuljannah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2020)
Education is a factor in building quality human resources. Student engagement in a university is important, because if student engagement is increased, the achievement of learning is increasing as well as, when the student engagement experiences a decline Learning was declining. This research aims to find out an influence of student engagement on student Faculty of Creative Industries Universitas Telkom Bandung with total population of 3033 active students with samples 354 from the calculation result using the formula Slovin. The method used is a survey with the incidental sampling technique, this research data using simple linear regression tests, the results gained on this research show that student Engagement has no significant effect on the study achievement in active students of the faculty of Creative Industries of Telkom University of Bandung. These results have been proven based on the H0 accepted hypothesis and H1 rejected that the student engagement has no significant influence on the learning achievement with a percentage of 0.1%, and the remaining 99.9% can be caused by other factors not examined in this study